Clinical Profile and Visual Outcome of Ocular Bartonellosis in Malaysia - Chai, Lee Tan; Lai, Chan Fhun; Li, Evelyn MinTai; Abdul Gani, Nor Hasnida; Muhammed, Julieana; Tuan Jaafar, Tengku Norina; Ahmad Tajudin, Liza Sharmini; Wan Hitam, Wan-Hazabbah (Hindawi Publishing Corporation, 2017)
Ocular bartonellosis can present in various ways, with variable visual outcome. There is limited data on ocular bartonellosis in Malaysia. Objective. We aim to describe the clinical presentation and visual outcome of ocular bartonellosis in Malaysia. Materials and Methods.This was a retrospective review of patients treated for ocular bartonellosis in two ophthalmology centers inMalaysia between January 2013 and December 2015. The diagnosis was based on clinical features, supported by a positive Bartonella spp. serology. Results. Of the 19 patients in our series, females were predominant (63.2%).The mean age was 29.3 years. The majority (63.2%) had unilateral involvement. Five patients (26.3%) had a history of contact with cats. Neuroretinitis was the most common presentation (62.5%). Azithromycin was the antibiotic of choice (42.1%). Concurrent systemic corticosteroids were used in approximately 60% of cases. The presenting visual acuity was worse than 6/18 in approximately 60% of eyes; on final review, 76.9% of eyes had a visual acuity better than 6/18. Conclusion. Ocular bartonellosis tends to present with neuroretinitis. Azithromycin is a viable option for treatment. Systemic corticosteroids may be considered in those with poor visual acuity on presentation.